X-ray backlighting of two-wire Z-pinch plasma using X-pinch - 赵彤 邹晓兵 张然 王新新 (Chinese physics B, 2010)
Two 50-μm Mo wires in parallel used as a Z-pinch load are electrically exploded with a pulsed current rising to 275 kA in 125 ns and their explosion processes are backlighted using an X-pinch as an x-ray source. The backlighting images show clearly the processes similar to those occurring in the initial stages of a cylindrical wire-array Z-pinch, including the electric explosion of single wires characterised by the dense wire cores surrounded by a low-density coronal plasma, the expansion of the exploding wire, the sausage instability （m = 0） in the coronal plasma around each wire, the motion of the coronal plasma as well as the wire core toward the current centroid, the formation of the precursor plasma column with a twist structure something like that of higher mode instability, especially the kink instability （m = 1）.